Evaluation of the interest of women assisted by the Centro de Atenção à Mulher (CAM) of Rio do Sul in intimate aesthetic surgeries - Eduarda Fritsche; Luiz Eduardo Mendes Zanis; Franciani Rodrigues da Rocha; Wagner Alves da Costa; Paola de Lima; Amanda Luísa Batista; Eloisa Fritsche (Revista Brasileira de Cirurgia Plástica, 2022)
Introduction: The term female genital surgery encompasses several techniques to improve the female vulvar area, both aesthetically and functionally. Feelings of emotional distress are common in women who seek such surgeries, significantly impacting their self-esteem, sexuality, hygiene and vulvar functionality. The objective is to To evaluate the interest of women assisted in a Women Care Center in intimate surgery. Methods: Observational study carried out at the Women Care Center (CAM) in Rio do Sul-SC. For data collection, a semi-structured questionnaire developed by the authors was used. Data were processed and grouped in Microsoft Excel, and descriptive data analysis was performed using the Statistical Package for Social Sciences (SPSS) program. Results: The findings indicated a great general interest in performing intimate aesthetic surgeries. Of the 100 women interviewed, 32 were interested in performing some intimate aesthetic surgery. Conclusion: Due to the importance given to intimate cosmetics in physical, psychosocial, sexual and everyday interference, with a major impact on the quality of life of these people, adequate resources must be allocated to a greater supply of such procedures in the Unified Health System for the population of Brazil.